2005
DOI: 10.1038/sj.emboj.7600705
|View full text |Cite
|
Sign up to set email alerts
|

Etd1p is a novel protein that links the SIN cascade with cytokinesis

Abstract: In animal cells, cytokinesis occurs by constriction of an actomyosin ring. In fission yeast cells, ring constriction is triggered by the septum initiation network (SIN), an SPB-associated GTPase-regulated kinase cascade that coordinates exit from mitosis with cytokinesis. We have identified a novel protein, Etd1p, required to trigger actomyosin ring constriction in fission yeasts. This protein is localised at the cell tips during interphase. In mitosis, it relocates to the medial cortex region and, coincident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 50 publications
8
60
1
4
Order By: Relevance
“…At restrictive growth temperatures, these etd1-deficient mutants exhibit a conventional sin-deficient phenotype, yielding elongated and multinucleate cells without a septum ( Jimenez and Oballe 1994;Daga et al 2005;Garcia-Cortes and McCollum 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At restrictive growth temperatures, these etd1-deficient mutants exhibit a conventional sin-deficient phenotype, yielding elongated and multinucleate cells without a septum ( Jimenez and Oballe 1994;Daga et al 2005;Garcia-Cortes and McCollum 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this analysis, we found that a pab1D null allele also suppressed lethality of etd1-deficient cells (data not shown). Since Etd1 is a positive regulator of SIN (Daga et al 2005;Garcia-Cortes and McCollum 2009), the ability of pab1-4 and pab1D to suppress etd1 mutants suggests that Pab1 might act as an inhibitor of the SIN pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations